Oxidative Stress in Poultry: Lessons from the Viral Infections - Rehman, Zaib Ur (Oxid Med Cell Longev, 2018)
Reactive species (RS), generally known as reactive oxygen species (ROS) and reactive nitrogen species (RNS), are produced during regular metabolism in the host and are required for many cellular processes such as cytokine transcription, immunomodulation, ion transport, and apoptosis. Intriguingly, both RNS and ROS are commonly triggered by the pathogenic viruses and are famous for their dual roles in the clearance of viruses and pathological implications. Uncontrolled production of reactive species results in oxidative stress and causes damage in proteins, lipids, DNA, and cellular structures. In this review, we describe the production of RS, their detoxification by a cellular antioxidant system, and how these RS damage the proteins, lipids, and DNA. Given the widespread importance of RS in avian viral diseases, oxidative stress pathways are of utmost importance for targeted therapeutics. Therefore, a special focus is provided on avian virus-mediated oxidative stresses. Finally, future research perspectives are discussed on the exploitation of these pathways to treat viral diseases of poultry.